PENDIDIKAN AGAMA ISLAM BERBASIS MULTIKULTURALISME (Studi Teks Mata Pelajaran PAI di SMA) - Kosim, Mohammad (STAIN Pamekasan, 2010)
Abstract: Multiculturalism is a concept that puts the community as a fundamental reality of cultural pluralism in public life. Although this terminology was first discoursed in America and Western Europe around the 1960s, but this term is not new for Muslims. This paper presents the study on multicultural education focusing on PAI Textbook in Senior High School. Conceptually, subjects relating to multicultural education are adequate, especially on the material relating to aqidah, history and the Holy Qoran.